The Effectiveness Of Using Google Meet In Online Learning To Improve Mathematical Communication Skills - Masta Hutajulu ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2022)
This research is motivated by the many problems that arise as a result of the corona 19 pandemic which requires learning to be done online. One of the problems that arise from online learning is the lack of effective use of online learning so that it can affect student learning outcomes including mathematical communication skills. The aims of this research are to find out and examine: 1) the implementation of online learning by using Google Meet to improve mathematical communication skills for Mathematics Education Students at IKIP Siliwangi. 2) the effectiveness of using Google Meet in online learning to improve mathematical communication skills for Education Students IKIP Siliwangi Mathematics. The methodology used in this research is descriptive quantitative. The data collection used in this research is by means of observation, pretest and posttest mathematical communication skills, and documentation. The result of this research is that the implementation of the use of Google Meet in online learning can improve students' mathematical communication skills. In addition, the effectiveness of using Google Meet to improve students' mathematical communication skills is very effective.